Therapeutic massage for college students with stress - José Antonio Torres Forjans; Miguel Angel Avila Solis; Jacqueline Medrano Montero; Yoel Ortiz Fernández; Rubier Pérez Hechavarría (Revista Información Científica)
Introduction: psychological stress in university students studying Bachelor of Tourism can cause negative manifestations in the psychological, physical and social order.